Evaluation of the growing and fruit bearing characteristics of the ‘Lapins’ sweet cherry cultivar grafted on rootstocks with different vigor - Csihon, Á.; Bicskei, K.; Dremák, P.; Gonda, I. (International Journal of Horticultural Science, 2017)
Sweet cherry is currently considered as a fruit with high interests. The amount of the produced yield is well saleable in the world and also in Hungary year by year, moreover often there is a shortage with the high quality fruits. Researches with the sweet cherry production focus on the intensity growing all over the world, namely the realization of producing with small trees ensuring high quality and quantity. In our examinations ’Lapins’ sweet cherry cultivar was evaluated grafted on rootstocks with different vigor (Gisela 5, Gisela 6, Colt) at the University of Debrecen, Pallag Experimental Station. According to our results trees grafted on Colt rootstock can be described with very low yields due to the excessive high vigor. Trees with Gisela 5 and Gisela 6 rootstocks showed excessive high productivity, as size of the fruits did not reach the required values.